Konsep Augmented Reality Sebagai Pengembangan Pemasaran Pariwisata dalam Menghadapi New Normal Masa Pandemi Covid-19 - Ellyta Tambunan; Anwari Masatip (Akademi Pariwisata Darma Agung, 2020)
The use of technology today in various sectors of life is very high, this can also seen from the needs and improvements provided by this digital service. Augmented Reality (AR) is one of the organizations that builds and improves online information today. The Covid-19 pandemic had a considerable effect on the use of this technology with the imposition of large-scale physical distancing, this depends on various sectors that exist today, especially the tourism sector. Therefore, it has a big impact on tourism activities / activities, both on a national and international scale (foreign) who will visit tourist spots / destinations. Augmented Reality has various features that support in various fields, one of which is traveling. The scientific and theoretical studies in this study provide a useful reference source for developers of mobile AR applications, tourism managers, and effective marketing strategies in facing the new normal era today. So that tourism businesses or tourist destinations better understand user preferences for mobile AR applications and others that are able to maintain behavior can still enjoy travel with their impulsivity in the context of tourism as a result.